The offer you can't refuse : what if customers want more than excellent service? - Van Belleghem, Steven, ....- (Leuven : LannooCampus, 2020)
"What if customers expect more than just a good product, excellent service and perfectly performing digital interfaces? And what if new technologies like 5G, artificial intelligence, quantum computing and robotics offer possibilities that go beyond mere ease of use? Digital ease of use is the new minimum. It has become a commodity. The customer now regards it as the most normal thing in the world to have access to limitless products and services with just a single click of a mouse. In the years ahead, companies will need to play an active role in the 'life journey' of customers: helping to make their dreams come true and removing problems from their daily lives. In addition, customers are looking increasingly to companies instead of governments to tackle societal challenges like climate change, health care and mobility. If your company succeeds in providing outstanding digital service, becomes a partner in the life of your customers and provides solutions for major societal issues, you will develop 'an offer you can't refuse'."
Keywords: Consumentengedrag